The Influence of Service Quality and Brand image on Purchasing Decisions at Optik Kurnia, Taman Walet Branch in Tangerang Regency - Ayu, Tresna Ratna; Purwanto, Agus (AGUSPATI Research Institute, 2025)
This study aims to analyze the influence of service quality and brand image on purchasing decisions at Optik Kurnia, Taman Walet Branch, Tangerang Regency. In the competitive optical industry, service quality and brand image are important factors that influence customer satisfaction and purchasing decisions. The method used in this study is a quantitative approach with a survey technique. The population studied consisted of 33 customers who used services at Optik Kurnia. Data were collected through a questionnaire designed to measure the variables of service quality, brand image, and purchasing decisions. Data analysis was carried out using multiple linear regression to test the proposed hypothesis. The results showed that service quality has a positive and significant influence on purchasing decisions with a significance value of 0.006. In addition, brand image also showed a positive and significant influence on purchasing decisions with a significance value of 0.000. The F test indicated that service quality and brand image simultaneously influence purchasing decisions with a significance value of 0.000. Based on these findings, it can be concluded that service quality and brand image have a significant influence on purchasing decisions at Optik Kurnia, Taman Walet Branch. Therefore, it is recommended that the company continue to improve service quality and strengthen brand image to encourage better purchasing decisions with a significance value of 0.015, while the work environment has a dominant and significant influence with a significance value of 0.000. Simultaneously, these two variables explain 69.8% of the variation in employee performance. This confirms that appropriate workload allocation and the creation of a conducive work environment are crucial for increasing productivity.